Industrial heritage, cultural resources of current industries and creative pioneers – utilizing Industrial Culture in Central Europe - Harfst, Jörn; Pizzera, Judith; Simic, Danko (Journal for Geography, 2016)
The paper deals with the framework conditions of Industrial Culture and the specific challenges in former industrialised towns outside agglomeration areas. To illustrate the use of Industrial Culture the paper gives a short Austrian example and finally discuss the main points about preservation and reactivation of industrial heritage.
Keywords: industrial heritage; industrial culture; tourism; Austria